Nephrolithiasis case in a beef cattle - Kizil, Omer; Han, M. Cengiz; Baydar, Ersoy (Ankara Univ Press, 2008)
The case material was 1 years old, male, Holstein beef cattle, complaint with anorexia, colic and constipation brought into Internal Medicine Clinic, University of Firat, Faculty of Veterinary Medicine. In clinical examination; painful blood-urine attempts at urination, slightly tympany and colic was determined. The cattle's disease was diagnosed as nephrolithiasis via laboratory analysis and ultrasonografic examination in the right paralumbar fossa.
Bir besi si?irinda nefrolitiazis olgusu
Keywords: beef cattle; nephrolithiasis